2016
DOI: 10.5114/ceji.2016.60993
|View full text |Cite
|
Sign up to set email alerts
|

Liver damage in primary biliary cirrhosis and accompanied by primary Sjögren’s syndrome: a retrospective pilot study

Abstract: IntroductionPrimary biliary cirrhosis (PBC) and primary Sjögren's syndrome (pSS) have been referred to as “generalized autoimmune epithelitis”. Indeed, the pathogenic mechanisms, clinical features, and optimal therapeutic approaches for them are not yet fully defined.Material and methodsA retrospective analysis was carried out on clinical data obtained from 302 inpatients newly diagnosed with PBC, pSS, or the coexistence of PBC and SS between May 2011 and December 2014. Forty-two patients with abnormal hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…It has been reported that 59% of patients with SS display cytoplasmic pattern positivity, and patients with autoimmune disease and cytoplasmic pattern positivity exhibit hepatic involvement [32]. Our study found that 85.4% of patients with SS ± PBC had a cytoplasmic pattern, which was similar to the 62.2-85.7% of patients with PBC reported in the literature [31,33] but higher than the 57.14% (4/13) of patients with SS ± PBC in the literature [33]. This may be due to the low case numbers in the literature, and the characteristic pattern of AMA (cytoplasmic granular type AC-21) was not separated from other cytoplasmic patterns in our study, which might have led to an overestimation of the results.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that 59% of patients with SS display cytoplasmic pattern positivity, and patients with autoimmune disease and cytoplasmic pattern positivity exhibit hepatic involvement [32]. Our study found that 85.4% of patients with SS ± PBC had a cytoplasmic pattern, which was similar to the 62.2-85.7% of patients with PBC reported in the literature [31,33] but higher than the 57.14% (4/13) of patients with SS ± PBC in the literature [33]. This may be due to the low case numbers in the literature, and the characteristic pattern of AMA (cytoplasmic granular type AC-21) was not separated from other cytoplasmic patterns in our study, which might have led to an overestimation of the results.…”
Section: Discussionsupporting
confidence: 87%
“…Of patients with PBC, 25% are asymptomatic at the time of diagnosis, but as the disease progresses, complications such as portal hypertension, osteoporosis, and liposoluble vitamin deficiency (vitamins A, D, E, and K) can occur (1,2) . PBC is associated with many other immune manifestations such as SS (75%) with eye involvement (2,3) , with AMA being positive in >90% of patients (3,5) . Our patient showed high AMA levels and, consequently to her disease, developed a severe secondary SS with multiple ocular perforations.…”
Section: Discussionmentioning
confidence: 99%
“…PBC is associated with many other immune manifestations such as and antimitochondrial antibodies (AMA), which occur in >90% of patients. Of patients, 75% develop secondary Sjogren syndrome (SS) with eye involvement (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 70% to 80% of patients complain of dry mouth; approximately 50% of patients present with intermittent alternating parotid swelling and pain involving one or both sides, and approximately 20% have liver damage, especially patients with autoimmune hepatitis or primary biliary cirrhosis. 9 SS occurs more often in women, and the age of onset is 40 to 50 years. SS can also occur in children.…”
Section: Discussionmentioning
confidence: 99%